Opportunities and Obstacles in Microbial Synthesis of Metal Nanoparticles - Poblete-Castro, I (John Wiley and Sons Ltd, 2023)
Metallic nanoparticles (MeNPs) are widely used in many areas such as biomedicine, packaging, cosmetics, colourants, agriculture, antimicrobial agents, cleaning products, as components of electronic devices and nutritional supplements. In addition, some MeNPs exhibit quantum properties, making them suitable materials in the photonics, electronic and energy industries. Through the lens of technology, microbes can be considered nanofactories capable of producing enzymes, metabolites and capping materials involved in the synthesis, assembly and stabilization of MeNPs. This bioprocess is considered more ecofriendly and less energy intensive than the current chemical synthesis routes. However, microbial synthesis of MeNPs as an alternative method to the chemical synthesis of nanomaterials still faces some challenges that need to be solved. Some of these challenges are described in this Editorial. © 2023 The Authors. Microbial Biotechnology published by Applied Microbiology International and John Wiley & Sons Ltd.